2022
DOI: 10.1101/2022.09.22.508899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental, social, and morphological drivers of fission-fusion dynamics in a social ungulate

Abstract: Social groups exist because individuals within the group accrue a net benefit from sharing space. The profitability of sociality, however, varies with ecological context. As ecological context varies, tension emerges among the costs and benefits of social grouping. Fission-fusion societies are fluid in their group dynamics across spatial and temporal contexts, permitting insights into how context affects whether animals choose to join or depart a group. We tested four non-mutually exclusive hypotheses driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Here, we found that the cohesion of mixed-species group was lower when zebras herded with wildebeest or buffalos than with impalas or giraffes. Conflicts of interests in decision making lower the cohesion of single-species group, such as observed in red deer (Cervus elaphus) or woodland caribou (Rangifer tarandus) (Conradt and Roper 2000;Sueur et al 2011;Le Goff et al 2024), and can be expected to constrain even more strongly the cohesion of mixedspecies group. Although zebras benefit from a lower risk of predation by herding with wildebeest than impalas (Schmitt et al 2014), the lower difference of habitat selectivity with impalas than wildebeest may explain the higher cohesion of zebras herding with impalas.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that the cohesion of mixed-species group was lower when zebras herded with wildebeest or buffalos than with impalas or giraffes. Conflicts of interests in decision making lower the cohesion of single-species group, such as observed in red deer (Cervus elaphus) or woodland caribou (Rangifer tarandus) (Conradt and Roper 2000;Sueur et al 2011;Le Goff et al 2024), and can be expected to constrain even more strongly the cohesion of mixedspecies group. Although zebras benefit from a lower risk of predation by herding with wildebeest than impalas (Schmitt et al 2014), the lower difference of habitat selectivity with impalas than wildebeest may explain the higher cohesion of zebras herding with impalas.…”
Section: Discussionmentioning
confidence: 99%
“…In part this was a decision made with respect to our data, as individuals from mostly separate clans were GPS-tagged, resulting in little observable influence between individuals. However, interacting covariates relating to conspecifics with temporal dynamics may lead to realistic patterns of social behaviour throughout the time-scale of interest, as there are likely to be fluctuations of attraction and repulsion to other individuals, for instance those that produce fusion-fission dynamics (Haydon et al, 2008;Silk et al, 2014;Le Goff et al, 2023). These fluctuations of social dynamics may relate to longer time-scales such cycles of breeding, although there may be fine-scale temporal dynamics that influence movement within a daily period.…”
Section: Discussionmentioning
confidence: 99%